A critical review speculating on the protective efficacies of autogenous Streptococcus suis bacterins as used in Europe - Rieckmann, Karoline (Porcine Health Manag, 2020)
BACKGROUND: Streptococcus (S.) suis is a major porcine pathogen causing high morbidity worldwide. This includes well-managed herds with high hygiene standards. In Europe, no licensed vaccine is available. As practitioners are obliged to reduce the use of antibiotics, autogenous S. suis vaccines have become very popular in Europe. MAIN BODY: Autogenous vaccines (AV) are generally neither tested for safety, immunogenicity nor protective efficacy, which leads to substantial uncertainties regarding control of disease and return on investment. Here, S. suis publications are reviewed that include important data on epidemiology, pathologies and bacterin vaccination relevant for the use of AV in the field. Differences between herds such as the porcine reproductive and respiratory syndrome virus infection status and the impact of specific S. suis pathotypes are probably highly relevant for the outcome of immunoprophylaxis using autogenous S. suis bacterins. Thus, a profound diagnosis of the herd status is crucial for management of expectations and successful implementation of AV as a tool to control S. suis disease. Induction of opsonizing antibodies is an in vitro correlate of protective immunity elicited by S. suis bacterins. However, opsonophagocytosis assays are difficult to include in the portfolio of diagnostic services. CONCLUSION: Autogenous S. suis bacterins are associated with limitations and risks of failure, which can partly be managed through improvement of diagnostics.